Abundance and Diversity of Aerobic Anoxygenic Phototrophic Bacteria in Polar Plant Microbiomes - Mäkinen, Emilia A.; Franz, Ole; Ihalainen, Janne A.; Helander, Marjo; Nissinen, Riitta; Mathew, Suni A.; Saloniemi, Irma; Saikkonen, Kari (Wiley, 2025)
Here, we examined the occurrence of plant-associated aerobic anoxygenic phototrophic bacteria (AAPB) across polar regions.Recently found in polar soils and cold- climate plants, AAPBs are photoheterotrophs that rely on environmental organic car-bon but capture solar energy via anoxygenic photosynthesis. We revealed the abundance of AAPBs by extracting bacteria fromplant tissues and imaging the colonies with bacteriochlorophyll-based near-infrared fluorescence. The taxonomic distributionof AAPBs was determined via 16S rRNA gene analysis. From the northern hemisphere, we describe AAPBs from the leafendo- and phyllospheres of numerous sub- and Arctic plant species in Northern Finland, Svalbard, and Greenland. In thesouthern hemisphere, we focused on AAPBs in the root and leaf endospheres and the phyllospheres of Deschampsia antarcticain Chilean Patagonia and maritime Antarctica. Additionally, we describe AAPB from the tissues of several other plant speciesin Patagonia. We found AAPBs commonly associated with the sampled plant species across both hemispheres. A diversity ofAlphaproteobacteria was found to contain the AAP capability: at all sampling sites, Sphingomonas was the most abundanttaxon (up to 60%), while Methylobacteria made up a notable proportion of sub-Arctic and sub-Antarctic AAPB samples (up to32%). In contrast to previous studies describing Methylobacteria frequently in various plant communities, AAP- containingMethylobacteria were virtually absent from our high-latitude sites. With diverse AAPB taxa found ubiquitously across polarregions and plant tissues, our results call attention to the potential ecological interaction between AAPBs and their planthosts.